Enhancing mechanical properties of styrene–butadiene rubber/silica nanocomposites by in situ interfacial modification with a novel rare-earth complex. (August 2016) - Zou, Yongkun; Sun, Yangkun; He, Jingwei; Tang, Zhenghai; Zhu, Lixin; Luo, Yuanfang; Liu, Fang
Abstract: In this study, a novel rare-earth complex, dithio-aminomethyl-lysine samarium (DALSm), was prepared and then was employed as activator, accelerator, cross-linker and interfacial modifier to improve the mechanical properties of SBR/silica nanocomposites. The results showed that 6 phr DALSm performed a higher vulcanization efficiency than the combination of 5 phr activator zinc oxide (ZnO), 2 phr stearic acid (SA), and 2 phr accelerator diethyl dithiocarbamate zinc (EDCZn). Meanwhile, the XPS and FTIR analysis of DALSm/silica model compounds confirmed that hydrogen bonds and coordination bonds could be formed between DALSm and silica during vulcanization process, which can effectively facilitate the homogenous dispersion of silica particles into SBR matrix and enhance the interface adhesion between rubber matrix and filler. As a consequent, the mechanical properties of SBR/DALSm/silica nanocomposites were substantially improved and much more excellent than those of the SBR/EDCZn/silica nanocomposites containing equivalent filler content. Based on the results of immobilized polymer layer, the reinforcing mechanism of DALSm in SBR/silica nanocomposites was analyzed.